Diagnóstico pré-natal de pentalogia de Cantrell associada a higroma cístico - Targa, Luciano Vieira; Rosa, Rafael Fabiano Machado; Betat, Rosilene da Silveira; Picetti, Jamile; Bedin, Chaiane; da Cunha, André Campos; Telles, Jorge Alberto Bianchi; Betineli, Ildo (Clinical and Biomedical Research, 2012)